Anton’s Syndrome due to Bilateral Ischemic Occipital Lobe Strokes - Sanela Zukić; Osman Sinanović; Lejla Zonić; Renata Hodžić; Svjetlana Mujagić; Edina Smajlović (Case Reports in Neurological Medicine)
We present a case of a patient with Anton’s syndrome (i.e., visual anosognosia with confabulations), who developed bilateral occipital lobe infarct. Bilateral occipital brain damage results in blindness, and patients start to confabulate to fill in the missing sensory input. In addition, the patient occasionally becomes agitated and talks to himself, which indicates that, besides Anton’s syndrome, he might have had Charles Bonnet syndrome, characterized by both visual loss and hallucinations. Anton syndrome, is not so frequent condition and is most commonly caused by ischemic stroke. In this particular case, the patient had successive bilateral occipital ischemia as a result of massive stenoses of head and neck arteries.